Training on Ablution Practices at DTA Andalusia Munjul - Farah Afifah Septiani; Risma Sukmayati; Yulianawati Yulianawati; Imam Tabroni; Snyder Bradford; Meredith Tandon (Yayasan Adra Karima Hubbi, 2023)
Background. This research focuses on ablution practice training. Purpose. Ablution activity is a series of actions (movements) washing and wiping certain body members, which begins with the intention and orderly done solely for the sake of expecting the pleasure of Allah Swt. Method. the method used is experimental quantitative method, data collection through pretest and posttest. Results. Based on the results of our research at DTA Andalusia, it was found that 1) students have mastered the material about ablution but in practice there are still those who cannot perform ablution movements properly, 2) there is an increase in students' ablution skills through practical ablution training. Conclusion. Therefore, practical training in wudhu is very necessary so that students are really able to implement it in their daily lives according to the pillars and sunnah.